(untitled) - Gilman, Michelle Rose (Indianapolis, IN, 2006)
Are you one of the millions of students taking the ACT? Have no fear! This friendly guide gives you the competitive edge by fully preparing you for every section of the ACT, including the optional writing test. You get two complete practice tests plus sample questions -- all updated -- along with proven test-taking strategies to improve your score.
Keywords: ACT Assessment,ACT đánh giá